A Qualitative Study on Urinary Tract Infections Among Adult Patients in Bost University Hospital, Helmand - Rahman Arian, Abdul; M. Tidman, Dr. Melanie; Khpalwak, Abdul Tawab; Khan, Ahmad (Clinical Medicine And Health Research Journal, 2023)
Urinary tract infections (UTIs) are the leading cause of hospital visits worldwide, significantly impacting patients with underlying illnesses. To effectively manage UTIs, it is essential to understand the causes of these conditions. This study aimed to determine the prevalence of UTIs and identify the contributing factors among adult patients attending Bost University Hospital (BUH). A cross-sectional study involved 1768 patients from the internal medicine department at BUH. Among these patients, 125 (7.07% of total visitors) were diagnosed with UTIs, 108 of whom were interviewed. The findings revealed that 57 of 108 patients (52.7%) experienced recurrent UTIs. Most diagnosed UTI patients were female (77.7%), and 92 of the 108 participants were married. The participants reported various signs and symptoms, including burning, dysuria, fever, frequency, abdominal pain, cloudy urine, urgency, chills, dribbling, and blood in urine. The outcomes of this study will provide valuable insights for researchers, policymakers, and public health organizations seeking to address the factors contributing to UTIs. However, it is essential to acknowledge the study's limitations, such as the relatively small sample size and the fact that it was conducted exclusively among patients visiting the outpatient department of BUH's internal medicine department. Although these findings may not represent the general population, they are a starting point for further research.